A single phase buck-boost AC-AC converter with low input current THD and high input power factor - Abedin, Amina Hasan; Kabir, Ashfanoor N M Enamul; Ahmad, Estiak; Rahman, Dhrubo; Choudhury, Mohammad Ali A Shoukat (© 2011 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 2011 International Aegean Conference on Electrical Machines and Power Electronics, ACEMP 2011 and Electromotion 2011 Joint Conference; Istanbul; Turkey; 8 September 2011 through 10 September 2011 [© 2011 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/ACEMP.2011.6490590